Trapped in Circulation: Repeated International Labor Migration in Lombok Island and Its Multidimensional Socioeconomic and Cultural Consequences (2004-2024) - Rahmat A Kurniawan (Lembaga Bale Literasi, 2026)
International labor migration has become a deeply ingrained livelihood strategy for many households on the island of Lombok, West Nusa Tenggara, Indonesia. Over the past two decades, migration has generated substantial remittance inflows and is widely regarded as a key source of household income and a pillar of the regional economy. However, this economic contribution has not been matched by a corresponding improvement in long-term well-being. Many home communities in Lombok continue to face persistent poverty, repeated out-migration, changes in family structure, declining engagement in agriculture, and shifts in local cultural practices. This study investigates the paradox of migration development in Lombok during the period 2004-2024. This study draws on official data from BP2MI, Bank Indonesia, BPS-NTB, the NTB Department of Manpower, and KNOMAD, and combines them with a systematic synthesis of 47 empirical studies. Using a mixed-methods longitudinal-analytical approach, this study examines migrant flows, remittance trends, destination patterns, and the broader economic, social, and cultural impacts of migration. Findings indicate that NTB recorded over 1.33 million documented migrant departures, with approximately 85% originating from four regencies in Lombok. During the same period, total remittances reached approximately Rp 61.07 trillion. Although these financial flows are associated with poverty reduction, increased school enrollment rates, and the expansion of small businesses, they have not yet created a stable foundation for local economic transformation. Instead, evidence points to rising social costs and a strong pattern of repeated migration, with 64.1% of returnees migrating again within three years. This study argues that migration in Lombok has evolved from a temporary livelihood strategy into a regime of structural dependency. Stronger policies are needed to channel remittances toward productive investments, human resource development, and community resilience.